2009
DOI: 10.1177/147323000903700614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Stress on Fetal Heart Rate Assessed by Vibroacoustic Stimulation

Abstract: This study was designed to determine whether maternal stress levels, state and trait anxiety levels, and stress hormones affect fetal heart rate (FHR) patterns after vibroacoustic stimulation (VAS) at 30 weeks of gestation. A total of 24 healthy pregnant women with a single fetus pregnancy were enrolled. Corticotropin releasing hormone (CRH) and adrenocorticotropic hormone in maternal plasma and cortisol, and chromogranin A in saliva were measured. The FHR patterns after VAS were divided into three types: type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…Although pregnancy loss in humans with elevated cortisol or diabetes may be multifactorial, changes in cardiac size and/or function in the fetus have been suggested as one factor contributing to late-term fetal loss in these pregnancies (34,35,41). Although it is enticing to hypothesize that the dramatic increase in stillbirths found in the present study is related to the changes in the fetal heart previously observed at 130 days of gestation in this model (8,31) and that have been found with glucocorticoid administration (12,20,32,37,43), there is no clear association with heart weight in this group of fetuses. However, in gestational diabetes there may be fetal diastolic dysfunction independent of hypertrophy (2).…”
Section: Perspectives and Significancecontrasting
confidence: 49%
See 1 more Smart Citation
“…Although pregnancy loss in humans with elevated cortisol or diabetes may be multifactorial, changes in cardiac size and/or function in the fetus have been suggested as one factor contributing to late-term fetal loss in these pregnancies (34,35,41). Although it is enticing to hypothesize that the dramatic increase in stillbirths found in the present study is related to the changes in the fetal heart previously observed at 130 days of gestation in this model (8,31) and that have been found with glucocorticoid administration (12,20,32,37,43), there is no clear association with heart weight in this group of fetuses. However, in gestational diabetes there may be fetal diastolic dysfunction independent of hypertrophy (2).…”
Section: Perspectives and Significancecontrasting
confidence: 49%
“…In diabetic pregnancies, fetal lactic acidosis and hypoxia have both been reported near term, and bradycardic episodes, ST segment depression, and fetal acidemia have been observed during labor in fetuses of both gestational and pregestational diabetic mothers (31,37,38), as well as heart failure with abnormal ECG during labor (19). An increased incidence of fetal bradycardic responses to fetal stress occurs in women demonstrating high anxiety during pregnancy (20). It is not known whether acidemia and bradycardia occur during labor in fetuses with Cushing's disease; however, in ovine fetuses, exposure to glucocorticoids appears to increase the bradycardia and acidemia during a hypoxic episode (9,11).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…For example, unstimulated FM is related to maternal psychological states such as anxiety, depression, anger and pregnancy‐specific stress (Conde, Figueiredo, Tendais, Teixeira, Costa, Pacheco, Rodrigues & Nogueira, 2010; DiPietro, Costigan & Gurewitch, 2003; DiPietro, Hilton, Hawkins, Costigan & Pressman, 2002b; DiPietro et al ., 2010; Field, Diego, Hernandez‐Reif, Salman, Schanberg, Kuhn, Yando & Bendell, 2002). Few studies have examined associations between maternal anxiety and depression and fetal heart rate response to stimulation (Allister, Lester, Carr & Liu, 2001; Makino, Matsuda, Yoneyama, Hirasawa, Takagi, Ohta & Konishi, 2009; Monk, Fifer, Myers, Bagiella, Duong, Chen, Leotti & Altincatal, 2010), and only a single study has examined and shown that maternal psychological state (depression symptoms) is associated with FM responses to VAS stimulation (Dieter, Emory, Johnson & Raynor, 2008). Further, both exogenous and endogenous glucocorticoids (GCs) are associated with unstimulated fetal motor activity (DiPietro, Kivlighan, Costigan & Laudenslager, 2009; Field, Diego, Hernandez‐Reif, Gil & Vera, 2005; Mulder, Koenen, Blom & Visser, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although measurement of stress during pregnancy is not easy, the STAI has been found to be a suitable tool for objectively measuring stress levels during pregnancy, because it clearly differentiates between the temporary condition of ‘state anxiety’ and the more general, long‐standing condition of ‘trait anxiety’ and has been adequately validated and checked for consistency . We previously demonstrated that the level of corticotropin releasing hormone, one of the markers of stress hormones, was significantly higher in individuals with high trait anxiety and concluded that STAI trait anxiety may be useful for evaluating chronic maternal stress …”
Section: Discussionmentioning
confidence: 99%